Delicate threads: A case study on velamentous placenta and its clinical significance - Smriti Anand; Dahiya, Pushpa; Shikha Madan; Sonia Dahiya (Asian Journal of Medical Sciences, 2024)
Velamentous placenta insertion is a rare and potentially serious pregnancy complication involving the abnormal attachment of the umbilical cord to the fetal membranes rather than to the placenta.This case report details the management of a 23-year-old primigravida at 38 weeks of gestation who presented to the labor room in spontaneous labor.Initial examination revealed a term-size uterus, vertex presentation, and moderate contractions,with a fetal heart rate of 144/min. Despite an unremarkable start to labor, persistent fetal heart decelerations post-amniotomy led to the discovery of velamentous insertion of the placental cord.This case discusses the challenges, decision-making process, and outcomes associated with this rare condition, ultimately resulting in an uneventful postoperative period and successful discharge on the 5th day for both mother and baby.